Digital research methods in fashion and textile studies - Sikarskie, Amanda (Bloomsbury Visual Arts, 2020)
Are you a researcher struggling to mine and make sense of a mountain of fashion data? Are you interested in learning about how digital methods and tools could enhance your research? Have you thought about ways to spark and engage in academic conversations on social media? Have you wondered how digital technologies are internationalizing the field of fashion and textile studies? Digital Research Methods in Fashion and Textile Studies presents the reader with a variety of digital methodologies to help build skills in searching for, analyzing, and discussing vintage design, photography, and writing on fashion, as well as historic and ethnographic dress and textile objects themselves. From advanced undergraduates and postgraduate students working on research projects to veteran professionals in fashion and textile history and beyond, everyone can benefit from a diverse set of fresh approaches to conducting and disseminating research. In the current age of instant gratification, with users snapping and posting images from runway shows long before the clothes will ever appear instores, the world of fashion is increasingly digital and fast-paced. Research on fashion is, too. Digital Research Methods in Fashion and Textile Studies will help you keep up in this rapidly changing world.